The state of lipid metabolism on the background of the use of ω -3 fatty acids in high-altitude conditions - Gulbarchyn Alisherovna Asrankulova; Zhyldyz Akmatovna Makhmudova; Zyinat Samidinovna Boronova; Meerim Taalaibekovna Taalaibekova; Zhyldyz Turusbekovna Ayipova; Unsun Satarkulovna Torobaeva (E3S Web of Conferences)
A study of the effect of high altitude (Tuya-Ashu Pass, 3200 m above sea level and Bishkek, 720 m above sea level) on rat metabolism demonstrated significant changes in the lipid profile and oxidative stress levels after three days of exposure to low oxygen availability. There was a significant increase in total cholesterol and triglyceride levels, indicating disturbances in lipid metabolism and may be indicative of hyperlipidemia. Low density lipoproteins (LDL) levels increased significantly, while high density lipoproteins (HDL) levels decreased significantly, which is likely associated with worsening cardiovascular health and an increased risk of atherosclerosis. Malondialdehyde (MDA) levels increased, indicating increased oxidative stress as a result of adaptation to high altitude conditions. Increased activity of superoxide dismutase (SOD) and catalase enzymes confirms that the rats’ bodies are trying to adapt to increased oxidative stress by activating free radical defense mechanisms. Oral administration of ω-3 fatty acids at a dose of 300 mg/kg of animal body weight once a day for 30 days leads to a decrease in the levels of atherogenic low-density lipoproteins, malondialdehyde, increase the level of anti-atherogenic high-density lipoproteins and activity of superoxide dismutase and catalase.